Jews and French Quebecers : Two Hundred Years of Shared History - Langlais, Jacques, 1921- (Book collections on Project MUSE., 1991)
Jews and French Quebecers recounts a saga of intense interest for the whole of Canada, let alone societies elsewhere. This work, now translated into English, represents the viewpoints of two friends from differing cultural and religious traditions. One is a French Quebecer and a Christian; the other is Jewish and also calls Quebec his home. Both men are bilingual. Jacques Langlais and David Rome examine the merging - through alterations of close co-operation and socio-political clashes - of two Quebec ethno-cultural communities: one French, already rooted in the land of Quebec and its relig.